A CREATIVE EXPRESSION OF CELEBRATIONS: RANGOLI - Thakur, Meenakshi (International Journal of Research -GRANTHAALAYAH, 2014)
Indian art has combined local tradition with outside influences, and has evolved along with a civilization, which has been remarkably innovative in all areas. The art has developed in the courts by the professional artists but folk art has developed in houses, worship places, courtyards, villages, among illiterate race. It is in fact an essential aspect of the celebrations in the family. India is a sub-continent and is composed of people with different cultures, different social customs and traditions and speaking different languages. Yet a stream of unity seems to run through the length and breadth of the country. It is this stream which in spite of all diversity keeps the country united. In Rangoli one can see the aesthetic expression of this unifying stream, with variation in styles and forms in different parts of the country. Rangoli is an Indian traditional - folk art, generally created on a floor on special festive occasions. The origin of this art can be traced to the “PURANAS”. The tradition of Rangoli originated in Maharashtra state and slowly disseminated to other parts of India. Almost invariably these are practiced only by women and take the form of drawings on the floor or on the walls of the house reflecting their creative artistic expressions. Their style and quality depended on the materials available in the place in which they were executed, these very factors that helps to identify the region. In Maharashtra it is called Rangoli, Sathiya in Gujrat, Mandma in Rajasthan, Alpanan in Bengal, Chowkapurna in Madhya Pradesh, Chaitrangana in Maharashtra, Puvidal in Kerala, Muggu in Andhra Pradesh, Rangoli in Karnataka, Kolam in Tamilnadu, Ahapan in Bihar. This decoration is done in every home in the nook and corner of the country though the decorative shapes and designs differ from place to place. The aim is to worship and celebrate the spiritual and divine existence by making the designs beautifully.